2023
DOI: 10.1093/mnras/stad065
|View full text |Cite
|
Sign up to set email alerts
|

Jet power, intrinsic γ-ray luminosity, and accretion in jetted AGNs

Abstract: The correlation between the kinetic jet power Pjet, intrinsic γ-ray luminosity (Lint) and accretion (Ldisk) may reveal the underlying jet physics in various black hole systems. We study the relation between kinetic jet power, intrinsic γ-ray luminosity, and accretion by using a large sample of jetted AGN, including flat-spectrum radio quasars (FSRQs), BL Lacertae objects (BL Lacs), gamma-ray Narrow-line Seyfert 1 galaxies (γNLS1s) and radio galaxies. Our main results are as follows: (1) The slope indices of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…It is generally believed that there is a close connection between jets and accretion. Many authors have confirmed this relationship (e.g., Rawlings & Saunders 1991;Cao & Jiang 1999;Ghisellini et al 2010Ghisellini et al , 2014Sbarrato et al 2014;Chen et al 2015Chen et al , 2023. We also study this relationship for radio galaxies.…”
Section: The Jet Power Versus Accretion Disk Luminositysupporting
confidence: 62%
“…It is generally believed that there is a close connection between jets and accretion. Many authors have confirmed this relationship (e.g., Rawlings & Saunders 1991;Cao & Jiang 1999;Ghisellini et al 2010Ghisellini et al , 2014Sbarrato et al 2014;Chen et al 2015Chen et al , 2023. We also study this relationship for radio galaxies.…”
Section: The Jet Power Versus Accretion Disk Luminositysupporting
confidence: 62%
“…The kinetic power is the key parameter to drive jet expansion, which is thought to be correlated with the black hole spin and mass [71,72,101] and the structure of the accretion disk [73,102,103]. The correlation between the jet kinetic power and black hole masses is indicated in several statistical analyses (e.g., [104][105][106]), while the observational correlation between the jet power and black hole spin is still a mystery (e.g., [107]). Except for the kinetic power, the size scale of an outflow in an individual object may be regulated by ages [95], inclination angle and interplay between jets and surrounding media [108].…”
Section: The Correlation Between the Size Scale Of Outflows And The M...mentioning
confidence: 99%